Trinidad and Tobago - (:unkn) unknown (T.Geddes Grant(Trinidad)Ltd.; Printed by Syncreators Ltd., 2009)
A little boy sitting next to a heap of pineapples and paw paw (Papaya).
Colour:Various colours;Style:Landscape;Other:Unborderd,Undivided
Keywords: Postcards; Trinidad and Tobago; Children; Fruit